2018
DOI: 10.1371/journal.pone.0202487
|View full text |Cite
|
Sign up to set email alerts
|

The gender suicide paradox under gender role reversal during industrialisation

Abstract: ObjectivesTo test for social structural effects on the gender paradox in suicidal behaviour.MethodsWe analyzed newspaper reports of completed and attempted suicides in the Scottish city of Dundee during the mass movement of women into the paid labour force in the 19th and early 20th Centuries. We calculated rates of suicides per 100,000 of the male and female populations.ResultsWe found that the female suicide rate dropped during this time period, whereas there was only a significant reduction in attempted sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…With regard to suicide rates which correlates with age, gender, and socioeconomic status ( 25 ), although females reported significantly higher rates of suicidal ideation (OR 1.32) ( 26 ); however, the ratio of male to female completed suicides was 1.97:1 ( 27 ). It has also been reported that compared with women, men were three times more likely to die from suicide ( 28 ).…”
Section: Challenges For the Female Preponderance Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to suicide rates which correlates with age, gender, and socioeconomic status ( 25 ), although females reported significantly higher rates of suicidal ideation (OR 1.32) ( 26 ); however, the ratio of male to female completed suicides was 1.97:1 ( 27 ). It has also been reported that compared with women, men were three times more likely to die from suicide ( 28 ).…”
Section: Challenges For the Female Preponderance Hypothesismentioning
confidence: 99%
“…The finding inspired the argument that higher suicide rates in males may result from the more lethal methods used by males to attempt suicide ( 30 ). However, in this study ( 29 ), attempted suicide was defined as “acts of self-inflicted injury or self-poisoning with overdose drugs,” which should be more accuracy with the term of “self-harm behavior.” Notably, in a recent review, the ratio of male to female non-fatal attempted suicides was 1.21:1 ( 27 ). Indeed, being male is reported significantly associated with all types of suicidal behavior ( 31 ).…”
Section: Challenges For the Female Preponderance Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Other socio-cultural differences are acceptability of suicidal behavior and availability of means for the suicidal act [37,56]. However, these bring back the discussion to the differences in suicide methods that are the key drivers of gender differences in the choice of suicide methods, which tend to be more lethal in men.…”
Section: Cultural and Social Normsmentioning
confidence: 99%
“…In the literature, some researches examined the difference in suicide rates between males and females, and observed the well-known philosophy of “gender paradox” in suicide—i.e., females typically have higher rates of suicide ideation, but lower rates of suicide mortality compared to males [ 23 , 24 ]. In addition to gender, other demographic factors can also play a critical role in linking to a higher suicide risk.…”
Section: Introductionmentioning
confidence: 99%